Tracing the Concept of ADR in SharÊ‘ah and Law – A Comparative Study - QAZI ATTAULLAH; LUTFULLAH SAQIB (Hamdard Islamicus, 2021)
The paper traces the concept of Alternative Dispute Resolution (ADR) in the SharÊ‘ah and law in general. The details of various modes of ADR (Arbitration, Mediation, Conciliation Negotiation, TaÍkÊm and ØulÍ) have been left aside, owing to the fact of concentration on the issue under investigation. In this work, focus, therefore, remains on ADR’s meaning, evolution, legal status, need and significance in both systems; with minute details. It also discusses the origin of ADR in the modern law, the various stages through which it has been passed, the era of invention of the phrase ‘ADR’ and the advantages of this mechanism of dispute resolution, both for the state and individual/individuals. As a complementary requirement, Pakistani Legal System has also been analyzed profoundly in the ADR perspective. It also discovers the similitude of term ‘ADR’ in the SharÊ‘ah. A comprehensive tabulated comparison between ADR and formal litigation is made in the present work, followed by a comprehensive conclusion of the issue under investigation. In addition, content analysis technique of qualitative research method has been used for the critical analysis of the secondary data, available on the concept of ADR and TaÍkÊm, both in the conventional and Islamic law respectively.